Determination of Construction Principles of Designs of Mobile Cluster Quantum Intellectual Nanorobots with Cluster Neurocomputer and Superneurocomputer - Rybak, L.; Kiptyk, V. (Інститут проблем штучного інтелекту МОН України та НАН України, 2009)
The article presents the results of the system research, determination and elaboration of cluster quantum
medical intellectual nanorobots with cluster neurocomputer and superneurocomputer on the basis of laws of
construction of modifications of intellectual nanorobots developed by the authors and modifications of
designs of natural intellectual nanorobots and their vocational orientation. У статті наведено результати системних досліджень, визначення та розробки кластерних квантових
інтелектуальних нанороботів з кластерними нейрокомп’ютером та супернейрокомп’ютером на базі
законів побудови модифікацій інтелектуальних нанороботів, розроблених авторами, та модифікацій
конструкцій природних інтелектуальних нанороботів та їх професійної орієнтації. В статье приведены результаты системных исследований, определение и разработки кластерных квантовых
интеллектуальных нанороботов с кластерными нейрокомпьютером и супернейрокомпьютером на базе
законов построения модификаций интеллектуальных нанороботов, разработанных авторами, и модификаций
конструкций естественных интеллектуальных нанороботов и их профессиональной ориентации